Microtomographic, Histomorphological, and Histomorphometric Analysis of Bone Healing in the Midpalatal Suture After Treatment with Isotretinoin - Maria Júlia Bento Martins Parreira; Daniela Vieira Buchaim; Ana Carolina Cestari Bighetti; Marcos Antonio Girotto; Miguel Ângelo de Marchi; Dayane Maria Braz Nogueira; Augusto Alberto Foggiato; Juliana Zorzi Coléte; Acácio Fuziy; Rogerio Leone Buchaim (Dentistry Journal)
Background/Objectives: Rapid palatal expansion is commonly used to correct maxillary deficiencies. However, medications like Isotretinoin may influence bone remodeling during treatment. Isotretinoin, a drug used to treat acne, was the focus of this study, which aimed to evaluate its effect on bone repair after rapid palatal suture expansion in rats. Methods: The sample consisted of 40 Wistar rats, divided into two groups: the control group (CG), subjected only to orthodontic movement, and the experimental isotretinoin group (IG), where movement occurred after drug administration. Periods of 0, 7, and 14 days after the installation of the orthodontic device were analyzed, with a force of 30 g applied in all groups using a steel spring. After euthanasia, the maxillae were removed and analyzed via Micro-CT, histologically, and histomorphometrically. Results: The results showed that the expander was effective in promoting the expansion of the palatal suture. After 14 days, the total expansion was 381% (CG) and 299% (IG); the percentage of vessels in the connective tissue increased by 145% in CG and 84% in IG; and bone formation in both groups occupied 52% of the expanded palatal suture. No significant differences were observed between the groups regarding collagen fiber formation. Conclusions: It was concluded that the daily administration of Isotretinoin at the standard dose for the treatment of severe acne does not cause significant alterations in the bone repair process following the opening of the median palatine suture in rats.